Use of immunohistochemical markers in clinical-morphological diagnostic of prostate diseases. - Grygorieva, J. (Морфологія / Morphologia / Morfologìâ, 2010)
High incidence and mortality rates of prostate cancer stipulate the necessity of new diagnostic approach development. The aim of investigation was the comparison of clinical and morphological methods of prostate disease patients examination and detection of necessity of immunohistochemical methods usage for optimisation of clinical-morphological diagnostic of prostate cancer. There were 169 patients of different age groups with prostate pathology that took part in the investigation. All of them were examined by serum prostate-specific antigen detection, digital rectal examination, transrectal ultrasound examination with transrectal needle biopsies, histological assessment and detection of AMACR and p63 (PIN coctail) expression. As a result of comparison the correlation between serum prostate specific antigen level and morphological changes in prostate tissue was developed. It was established that simultaneous usage of AMACR and p63 helps to differentiate cancer and pretumor conditions in difficult cases. So, to establish a correct diagnose and prognosis of disease it is necessary to use complex diagnostic approach.